Kemampuan Adaptasi Kepiting Bakau (Scylla serrata) Terhadap Perubahan Salinitas Air = MUD CRAB (Scylla acetate) ADAPTATION ON WATER SALINITY CHANGE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT: Objectives of this research were to know water salinity change which can be used for culturing and fattening of mud crab, and to knoW adaptation of mud crab on water salinity change. The reseearch used modified bioassay method and completelly randomized factorial design consisted of two factors namely water salinity change (0,5 and 10 ppt of water salinity change) and duration of water salinity change (3 and 6 hours). The results indicated that decreasing salinity by 5 and 10 ppt per 3 and 6 hours from 20 to 0 ppt could be adapted by mud crab. As well as increasing if salinity by 5 and 10 ppt per 10 and 6 hours from 20 to 50 ppt could be adapted by mud crab. Mud crab was able to adapt water salinity change by 5 and 10 ppt per 3 and 6 hours from 0 to 50 ppt,